ChemInform Abstract: Alginic Acid Aerogel: A Heterogeneous Broensted Acid Promoter for the Direct Mannich Reaction. Issue 43 (October 2015) - Pettignano, Asja; Bernardi, Luca; Fochi, Mariafrancesca; Geraci, Lorenzo; Robitzer, Mike; Tanchoux, Nathalie; Quignard, Francoise
Abstract Highly dispersed alginic acid aerogel beads are used as heterogeneous promoters in the three‐component direct Mannich reaction giving amines in high yields as diastereomeric mixtures.